The effectiveness of celebrity endorsements in Polish magazines - Kowalewska, Kinga (Annales. Etyka w Życiu Gospodarczym, 2019)
Due to several cognitive processes, celebrity endorsements are effective in increasing sales. The presence of a famous person in an advertisement can command extra attention which may translate into an increase in sales. The aim of the paper is to show the scale of popularity of endorsement in Polish press advertisements in selected magazines directed at different target groups. The study relies, in part, on qualitative content analysis, and uses a survey to determine the effectiveness of celebrity endorsement as a marketing strategy in building trust around a given brand or product and the credibility of an advertising message among its target audience. The final section of the research presents the recall rates for brands/product and their endorsers. Generally, it has been found that celebrity endorsement as a marketing strategy more popular in Poland than in the USA, and a number of particular criteria have to be met in order for it to be efficient. The data reveal that the names of the endorsing celebrities are more strongly associated with advertised products and brands, than the products or brands with their endorsers’ names.